Calidad de vida relacionada con las actividades de vida diaria del adulto mayor. Riobamba, 2018-2019 - Samy Carolina, Gordillo Erazo (2021)
ABSTRACT The study of the perception of quality of life of the elderly is necessary to contribute to the senior years and achieve active aging. This study aimed to determine the perception of the quality of life of the elderly living in San Luis Parish. To accomplish the aim of this study, the researcher used basic, retrospective, descriptive, and correlational research. Two hundred and five elderly participated as the population in this study. The researcher analyzed medical records using Pearson's correlation to identify the relationship between quality of life and functional capacity. Participants' ranged in age of 69.27 years with a predominance of female adults (61.46%). Additionally, 82.44% of participants suffered from different types of diseases, such as arterial hypertension (34.32%), hypothyroidism (28.99%), and diabetes mellitus (18.34%). The elderly with inadequate quality of life (57.07%) and functional disability (76.10%) predominated; both elements were affected as the age of older adults increased. Among older adults with disabilities, minor disability was the predominant one (44.23%). This study concluded that there is a significant positive relationship between the functional capacity and quality of life scores in the elderly living in San Luis parish, Riobamba, concerning activities of daily living. Keywords: Elderly, Quality of life; Functional ability. . Reviewed by: MsC. Adriana Cundar Ruano, Ph.D. ENGLISH PROFESSOR C.C. 170926853